2014
DOI: 10.3389/fmicb.2014.00165
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of salt in catalysis and maintaining structure of halophilic proteins against denaturation

Abstract: Search for new industrial enzymes having novel properties continues to be a desirable pursuit in enzyme research. The halophilic organisms inhabiting under saline/ hypersaline conditions are considered as promising source of useful enzymes. Their enzymes are structurally adapted to perform efficient catalysis under saline environment wherein n0n-halophilic enzymes often lose their structure and activity. Haloenzymes have been documented to be polyextremophilic and withstand high temperature, pH, organic solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 47 publications
3
42
0
2
Order By: Relevance
“…Halophilic proteases, apart from being highly salt stable, have also been recognized for their polyextremophilicity, as evident from their increased resistance to denaturation by higher temperatures, chemical reagents, detergents, chaotropic agents, organic solvents and extreme pH values [22,23]. Immobilization of these enzymes would therefore add to enhance such properties and provide ample scope for expanding their versatility.…”
Section: Introductionmentioning
confidence: 98%
“…Halophilic proteases, apart from being highly salt stable, have also been recognized for their polyextremophilicity, as evident from their increased resistance to denaturation by higher temperatures, chemical reagents, detergents, chaotropic agents, organic solvents and extreme pH values [22,23]. Immobilization of these enzymes would therefore add to enhance such properties and provide ample scope for expanding their versatility.…”
Section: Introductionmentioning
confidence: 98%
“…However, low‐salt conditions destabilized ADH/A1a, possibly because of the increased structural flexibility and partial unfolding promoted by the decline in external ionic forces . Notably, the presence of salt is expected to play an important role in the structural protection of halophilic proteins . Furthermore, ADH/A1a was able to withstand exposure to organic solvents.…”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of ions in salt solutions reduces both water activity and available water molecules, which are required for making a water layer around proteins [193]. The special amino acid compositional features of halophilic proteins are the key reasons for their high solubility in aqueous solutions containing high salt concentrations and their resistance to organic solvents [194].…”
Section: High-salt Adaptation Of Haloenzymesmentioning
confidence: 99%
“…Acidic residues are more abundant on the surface of halophilic proteins in comparison with their non-halophilic counterparts. These negatively charged residues compete with salt for hydration [195] and accumulation of water molecules around the halophilic proteins prevents their aggregation, even at high salt concentrations [193]. It has been shown that there are more acidic residues (especially aspartic acid) than basic ones on a halophilic protein surface, which explains the acidic nature of halophilic proteins.…”
Section: High-salt Adaptation Of Haloenzymesmentioning
confidence: 99%